2019
DOI: 10.1108/ajar-09-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

Building a bulletproof whistleblowing environment: an accountant’s perspective

Abstract: Purpose The purpose of this paper is to assess the appropriateness of the factors that contribute to building a better whistleblowing environment and culture within an organisation and provide guidelines on how to build a better whistleblowing environment within an organisation. Design/methodology/approach In total, 592 questionnaires were circulated to 148 accounting firms licensed to carry out statutory audits of public limited companies expecting responses from 4 stakeholders from each entity. Out of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…As a result, the reporting will be acknowledged as legitimate behavior by the organizations. It was found that reporting channels influence whistleblowing intentions (Rajeevan, 2020;Kanojia et al, 2020). Therefore, the fourth hypothesis is derived as below: H4: There will be a significant relationship between reporting channels and whistleblowing intention among public sector employees in the northern region of Malaysia.…”
Section: Responsiveness Of Management and Whistleblowingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the reporting will be acknowledged as legitimate behavior by the organizations. It was found that reporting channels influence whistleblowing intentions (Rajeevan, 2020;Kanojia et al, 2020). Therefore, the fourth hypothesis is derived as below: H4: There will be a significant relationship between reporting channels and whistleblowing intention among public sector employees in the northern region of Malaysia.…”
Section: Responsiveness Of Management and Whistleblowingmentioning
confidence: 99%
“…There has been a debate among previous researchers on the relationship between financial reward and whistleblowing. Whistleblowing behavior should be regarded as the norm and should not be rewarded because normal behavior does not merit a bonus, and it may also lead to false reports for personal advantage, such as claiming rewards (Teichmann & Falker, 2021) or inflicting reputational damage on organizations (Rajeevan, 2020). However, some researchers stated that the financial reward may motivate the whistleblowing intention.…”
Section: Responsiveness Of Management and Whistleblowingmentioning
confidence: 99%
“…Ismail et al (2018) show that the organizational structure of audit firm has a significant effect on the whistleblowing practices. Rajeevan (2020) indicates that the most important factor affecting whistleblowing is the existence of organizational culture that encourages employees to whistle. The third category of factors is those factors related to the whistleblower.…”
Section: Whistleblowing In Accounting Contextmentioning
confidence: 99%
“…The "litany" of fraud scandals (Lokanan 2015), the collapse of leading accounting firms (Rajeevan 2020), the plethora of corruption cases (Anand et al 2004), and the general public's suspicion and loss of trust in institutions that ensure transparency and accountability has brought together governments, institutions and academic researchers in the fight against fraud and its typologies (corruption, nepotism, misappropriation of assets, embezzlement, cronyism), crimes that threaten the financial stability of organizations both in the public and private sectors. Even during the worldwide crisis of the COVID-19 pandemic, fraudulent activities have taken place (Murrar 2021;Levi and Smith 2021;Karpoff 2021) in which huge amounts of money were distributed in violation of standard procedures (Bajpai and Myers 2020).…”
Section: Introductionmentioning
confidence: 99%